The COVID-19 Crisis and the Global Compact on Migration: The Momentum and the Tool to Overcome “Immobility” - Delas, Olivier; Jouzier, Baptiste (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2022)
After some forty years of security and closure discourse towards international migration, and of “crisis” management in the matter, the adoption of the Global Compact for Safe, Orderly and Regular Migration (GCM) in December 2018, although a non-legally binding instrument, seems to be able to lead to an overcoming of this approach, which is visibly counterproductive. Thus, states commit to “[e]nhance availability and flexibility of pathways for regular migration” (Objective 5) or “[s]trengthen certainty and predictability in migration procedures” (Objective 12). Through the idea of global cooperation, based on law, the ambition of states to adopt a more long-term approach to the migration phenomenon emerges. However, the COVID-19 crisis seemed to greatly diminish the prospects of implementing such an approach. The desire to limit the spread of the virus quickly led to a strict closure of borders, drastically reducing migration flows. The multilateral approach to this issue seemed to be quickly swept aside by national concerns: the initial reactions of the European Union Member States were a clear example. However, this borders closure, taken to its extreme for health reasons, has highlighted the migrant labour dependency of the economies of the “global North”. If the crisis stroke migration and international mobility in the short term, it is not certain that in the mid to long term, the consequences of the health crisis will not, on the contrary, lead to a reconsideration of the security and closure approach implied by crisis management. Indeed, the shortage of migrant workers, linked to the closures brought about by the COVID-19 crisis, has led to radical state responses — from the organisation of “charter” flights to facilitate the arrival of migrant workers to the regularisation of illegal workers or rejected asylum seekers — or, where states failed, to “underground” responses — labour migration having been managed mainly by the Mafia in Italy, for example. Therefore, it seems necessary to wonder if, in a way, the COVID-19 crisis, through the paroxysm of border closure it has brought and the needs it has thus underlined, could not constitute a momentum for the implementation of a new approach to international migration, as advocated by the GCM.